PENGARUH MEDIA TANAM DAN PUPUK NPK 16:16:16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKIS SAYUR (Diplazium esculentum S.) - Nescaya Suhendri; T. Rosmawaty; Raisa Baharuddin (UIR Press, 2018)
ABSTRACT The purpose of this study was to determine the interactions and main effects of planting media and NPK 16:16:16 fertilizer on growth and production in vegetable ferns (Diplazium esculentum S.). The design used is a Factorial Complete Random Design. The first factor is the planting media of peat soil and mineral soil consists of 3 levels of treatment, namely: peat soil, mineral soil and a combination of 1: 1 peat and mineral soil while the second factor is NPK 16:16:16 fertilizer with 4 levels of treatment, namely: 0, 0.3, 0.6 and 0.9 g / polybag so that 12 treatment combinations were obtained, with 3 replications, then a total of 36 experimental units were obtained. Each unit consists of 4 plants with 2 plants used as samples. Observation parameters consisted of the age of emergence of shoots, plant height, number of young leaves, economical wet weight and dry weight. The results showed that the interaction of planting media and NPK 16:16:16 fertilizers gave a real influence on the number of young leaves with the best treatment was the planting media of a combination of peat and mineral soil 1: 1 and 0.6 g NPK fertilizer 16:16:16 (M3N2 ). The main effect of the planting medium was evident on the parameters of plant height, number of young leaves, economic wet weight, and dry weight. The best treatment is found in a combination of peat and mineral media 1: 1 (M3). The main effect of NPK 16:16:16 was significantly affected by the number of young leaves, economic wet weight and dry weight with the best treatment of 0.3 g (N1). Keywords: Growing media, NPK Fertilizer, Vegetable Fern